PERANCANGAN LOGO, BUKU MENU DAN ILUSTRASI BANNER UNTUK MEMPERKUAT BRANDING WARUNG MIE AYAM MAK ATIK DI TAWANGMANGU - Kurniawan, Daniel Ferry; Lero, George Bryan; Betteng, Albert Deren Theofilus (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This research was conducted because Warung Mie Ayam Mak Atik in Tawangmangu has not had a clear visual identity since it was established in 2008. This shop does not have a logo, menu book, and banner illustration that can strengthen branding and attract customers. The research method used is qualitative, with direct observation and interviews with Mrs. Atik as the business owner to understand her visual needs. The result of this study is the design of a visual identity that includes logo design, menu book, and banner illustration with a natural concept. It is hoped that this more professional visual identity can help increase customer appeal, strengthen brand image, and make Warung Mie Ayam Mak Atik better known in Tawangmangu.